Observations on Orchids and Euglossine Bees in Panama and Costa Rica - Dressler, Robert L. (1967)
Many orchid flowers and sorne flowers of other families produce no nectar and are visited and pollinated primarily or exclusively by male euglossine bees. These bees brush on the surface of the flower with tufts of hair on the forefeet, and gather sorne aromatic substance which is then placed in their inflated hind tibiae. The bees are attracted by odor, and many of the flower odors are highly specific, attracting one or few bee species. The tribe Euglossini includes Euglossa, Eulaema, Euplusia, Eufriesea, and the parasitic genera Aglae and Exaerete. All genera of the orchid subtribe Stanhopeinae are pollinated by euglossine bees; observations are given here for Acineta superba, Coeliopsis hyacinthosma, Coryanthes maculata, Gongora (5 or 6 species), Kegeliella atropilosda, Lacaena spectabilis, Paphinia clausula, Peristeria (2 species), Polycycnis gratiosa, Sievekingia (2 species) and Stanhopea (3 species) . All members of the subtribe Catasetinae are also pollinated by euglossine bees, and observations are given for all three genera: Catasetum (3 species), Cycnoches (6 species) and Mormodes (7 species). Other orchid genera far which observations are given here are: Dichaea, Kefersteinia, Lycaste and Notylia.Euglossine pollination provides very effective isolating mechanisms, and has been important in the speciation of several orchid groups. Isolation by highly selective fragrance might permit sympatric speciatíon through odormodifying mutatian. Orchid species with sympatric cIose allies tend to be more specific in their pollination relationships than geographically isolated species. While the pollination relationships are highly specific, the same bee species may visit and pollinate several different (and distantly related) orchid species. In several cases, archid flowers attract "accessory visitors", bees which do not function pollinators because of size or behavior. In general, euglossine pollination appears to be efficient, and the more advanced orchid species appear to be more efficiently pollinated than their primitive allies.